The comparative study of intravenous Ondansetron and sub-hypnotic Propofol dose in control and treatment of intrathecal Sufentanil-induced pruritus in elective caesarean surgery - Anahita Hirmanpour; Mohammadreza Safavi; Azim Honarmand; Akram Zavaran Hosseini; Maryam Sepehrian (Wolters Kluwer Medknow Publications, 2015)
Objective: Pruritus is a common and disturbing side effect of neuraxial opioids after cesarean section. The purpose of this study was to compare the efficacy of intravenous ondansetron and sub-hypnotic dose of propofol in control and treatment of intrathecal sufentanil induced pruritus in cesarean surgery. Methods: Totally, 90 parturient with American Society of Anesthesiology physical status grade I-II, undergoing spinal anesthesia with 2.5 μg sufentanil and 10 mg bupivacaine 0.5% were enrolled to this randomized, prospective, double-blind study. The women were randomly assigned to two groups who received 8 mg ondansetron or 10 mg propofol to treat pruritus grade ≥3. The patient was evaluated after 5 min and in the lack of successful treatment, the doses of two drugs repeated and if the pruritus is on-going, the exact treatment with naloxone was done. Findings: The incidence of pruritus was 69.3%. Both groups were well-matched. The peak time pruritus was 30-75 min after injection. The percentage of individuals consumed naloxone were 6.8% and 15.9% in ondansetron and propofol groups, respectively (P = 0.18). The mean score of satisfaction (according to visual analog scale criteria) was 9.09 ± 1.1 in ondansetron group and 9.3 ± 1.07 in the propofol group (P = 0.39). Conclusion: Ondansetrone and sub-hypnotic dose of propofol are both safe and well-tolerated. Due to their same efficacy in the treatment of intrathecal sufentanil-induced pruritus, they can be widely used in clinical practice.